KINERJA KEUANGAN BANK PEMBANGUNAN DAERAH DI JAWA DAN DI LUAR JAWA - Ardian Prima Putra; Gustita Arnawati Putri; Purwanto Purwanto (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to measure empirically the influence of banking intermediation factors (LDR), operational efficiency and credit risk (NPL), capital adequacy (CAR), on the financial performance of Regional Development Banks in Indonesia, besides wanting to see whether there are differences the performance of BPD banks in Java and outside Java registered with the Financial Services Authority. The period used is from 2014 to 2019. This study is a comparative quantitative study that uses multiple linear regression analysis techniques and uses a different test to see whether there is a difference in performance. The results show that the LDR, efficiency, NPL and CAR variables simultaneously have a significant effect on the performance of Return on Assets at Regional Development Banks outside Java. While the LDR, efficiency, NPL and CAR variables have no simultaneous effect on return on assets at regional development banks located in Java. The results also show that there are differences in the performance of regional development banks in Java and outside Java, especially in efficiency and Non-Performing Loan variables. Keywords : Efficiency, LDR, NPL, CAR , Performance